Suitability analysis of scrubland for arabica and robusta coffee plants in Aceh Besar Regency. Issue 1 (January 2021) - Fachruddin, F; Fadhil, R; Syafriandi; Dahlan, D
Abstract: This study aimed to analyze the land suitability for arabica (Coffea arabica) and robusta (Coffea canephora) coffee in scrubland in Aceh Besar Regency. This was implemented because the potential area of scrubs that were not utilized properly in Aceh Besar Regency reached 2, 5330.6 ha. The data used in this study were secondary data and primary data, while data processing techniques were carried out by analyzing climate data, determining land map units, and taking soil samples in the field. Stages of combining several parameters were done by using Quantum GIS (QGIS) software using matching between land characteristics and land suitability class criteria. The results showed that the suitability of scrublands for coffee cultivation in the scrublands of Aceh Besar Regency was more suitable for robusta coffee cultivation, where after the improvement process was done, the potential land suitability to be moderately suitable (S2) with an area of 13, 240.8 ha (52.3%), according to marginally suitable (S3) covering an area of 11, 982 ha (47.3%) and not suitable (N) only an area of 107.8 ha (0.4%). The unsuitability limiting factor (N) for robusta coffee cultivation was only found at SPL 2 with Slope Class inhibition> 40%. As for the suitability of scrubland for Arabica coffee cultivation in Aceh Besar Regency, it had a fairly severe limiting factor on all land map units (SPL), including parameters of average temperature and altitude with no suitable class category (N), so the improvement process could not be done.